Crystallization: Effects of Stereoisomerism on the Crystallization Behavior and Optoelectrical Properties of Conjugated Molecules (Adv. Mater. 27/2013). (12th July 2013) - Liu, Jianhua; Zhang, Yuan; Phan, Hung; Sharenko, Alexander; Moonsin, Preecha; Walker, Bright; Promarak, Vinich; Nguyen, Thuc‐Quyen
<x xml:space="preserve">Abstract</x> Three stereoisomers of a diketopyrrolopyrrolecontaining conjugated molecule are separated and identified to investigate the effects of stereoisomerism on the crystallization behavior and optoelectrical properties of the material. The investigation by Thuc‐Quyen Nguyen and co‐workers on page 3645 reveals useful hints to address two primary experimental challenges for complicated conjugated molecules, i.e., how to grow well‐defined single crystals, and the polymorphism of crystal structures. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>